Occurrence of Pseudosida ramosa Daday, 1904 (Crustacea: Cladocera: Ctenopoda) in marginal lakes of the Paranapanema River, with comments on its distribution. - Debastiani Junior, J.R.; Nogueira, M.G.; Elmoor-Loureiro, L.M.A.; Perbiche-Neves, G. (My University, 2009)
Aim: Contribute to the understanding of the distribution of a littoral cladoceran, Pseudosida ramosa Daday, 1904, in Brazil, with special reference for the Paranapanema River basin (Southeast Brazil); Methods: The specimens were sampled in two floodplain lakes located in the middle Paranapanema River basin, in the boundary of São Paulo and Parana States, using a standard plankton net (50 [mu]m mesh size). Trinocular microscopic with camera lucida and milimetric scale was used for the observation and measurements of the specimens; Results: Only three individuals were found (in winter and summer), despite of an extensive sampling program during 17 consecutive months of observations in both lakes. The largest body length was 1,146 [mu]m. The taxonomical identification followed Korovchinsky (1992); Conclusions: This species have a wide geographical distribution in Brazil, but it is restricted to zones colonized by aquatic macrophytes and seems to occur in low population abundance. The scarcity of registers of P. ramosa demonstrates the necessity of deeper investigations of littoral habits as well as the important role of this kind of environment for the conservation of the rivers/reservoirs biota, including some possible rare species.
Ocorrência de Pseudosida ramosa Daday, 1904 (Crustacea: Cladocera: Ctenopoda) em lagoas marginais do Rio Paranapanema, com comentários sobre sua distribuição